Costly Gains to Breaking Up: Lecs and the Baby Bells - Ying, John S.; Shin, Richard T. (The Review of Economics and Statistics, 1993)
While the divestiture of AT&T was intended to produce benefits in the long-distance market, the evidence suggests it has created an unexpected side benefit in local telephone markets. The authors' results show that local exchange carriers have realized immediate cost savings in responding to competitive pressures since the breakup, with the baby Bells experiencing generally larger gains. Dynamically, these productivity gains have increased over time at a relatively constant rate. Although gains of 3-5 percent of total cost are not that large, the absolutely large costs of telephone companies imply significant cost savings of nearly $72 million for the representative firm. Copyright 1993 by MIT Press.